A nutraceutical formulated drink from edible bird‟s nest and collagen with high bioavailability properties - Nadaraju, Shamala Devi (2022)
Nutraceuticals drinks formulated from phytochemicals or functional foods that contain natural bioactive and chemical compounds contributes to health-promoting, disease-preventing or therapeutic properties. In current trends, there is a high demand for nutraceutical products and functional food, particularly drinks or beverages. Formulation of nutraceutical drink containing Edible Bird Nest‟s (EBN) extract and collagen type II can result in preventing bone health disease as it gives great benefits and improve the bone strength. The aim of this study is to develop a nutraceutical drink from EBN extract and collagen type II for bone health properties with high bioavailability of collagen content. In this study, six different formulation was carried out with different concentrations of EBN extract (0%, 0.03% 0.025%, 0.050%, 0.075%, 1%) and two samples of collagen drink were purchased for benchmarking from market such as Kinohibitsu and Ecolite. All sample were analysed with in vitro bioavailability analysis and sensory analysis using Hedonic Test. Findings indicated that F4 (formulation 4) with 1% of EBN extract and 0.03% collagen type II showed the best results and contribute to high bioavailability of collagen (85.61%) when comparing with formulation of EBN extract with C1 (control 1) 0.03% of collagen type II, without EBN and F1 0.03% of collagen type II, EBN 0.025%. Findings indicated that with the increase in the addition of EBN extract caused significant difference (p<0.05) in absorption of total collagen into the body when compare with C1 and F1. Sensory analysis findings revealed EBN collagen drink of F4 with 1% of EBN extract and 0.03% collagen type II is the most preferred among consumers. It caused significant difference (p<0.05) in appearance, color, aroma, taste and overall acceptability for sensory analysis. In summary, nutraceutical drink of formulation 4 of 1% EBN extract and 0.03% collagen type II has high bioavailability of collagen and consumer acceptability.